Life cycle phenology, secondary production, and trophic guilds of caddisfly species in a lake-outlet stream of Patagonia - Brand, Cecilia (2012)
Lake-outlets are transitional areas recognized as highly productive ecosystems in terms of density and biomass of aquatic insects. Life cycle, secondary production, trophic guilds and environmental constraints of caddisfly assemblages were investigated on a natural lake-outlet stream (Nant y Fall) in Patagonia, Argentina. We investigated the site monthly from May 2007 to April 2008 by recording environmental data and sampling caddis larvae using a Surber sampler at riffle areas (n=36). Mastigoptila longicornuta, Smicridea annulicornis, Smicridea frequens, Brachysetodes quadrifidus and Parasericostoma ovale displayed well synchronized univoltine life cycles, while Neoatopsyche brevispina, Neopsilochorema tricarinatum, showed an asynchronous development pattern, although most of them had an extended recruitment, similar to those reported for non lake-outlet streams in the area. Annual secondary production per species varied from 8.22 (B. quadrifidus) to 3568.83mgm -2y -1 (P. ovale), with overall caddisfly production amounting to 4.8gm -2y -1. Shredder/collector-filterer ratio was 3.3/1 suggesting that the system was detrital based. Redundancy analysis indicated that seasonally dynamic variables such as discharge, benthic particulate organic matter and temperature were the main predictors of seasonal caddisfly assemblage variation. We propose that the variety of food resources and the significant spatial heterogeneity at lake-outlet streams contribute to sustain a rich caddisfly community.